Projectile Point Reworking: An Experimental Study of Arrowpoint Use Life. Issue 2 (29th April 2019) - Loendorf, Chris; Rogers, Thatcher; Oliver, Theodore J.; Huttick, Brian R.; Denoyer, Allen; Woodson, M. Kyle
Abstract : This article summarizes the results of controlled experiments in which flaked-stone points that varied in impact strength by a factor of almost three were shot at media that were increasingly inelastic and therefore likely to break the points. Broken tips were reworked if possible, and used again under the same conditions. Our results show that all damage to low impact-strength materials, especially obsidian, was generally catastrophic, and, consequently, these points could only rarely be reworked. The fact that low-strength stones were commonly used to make small arrowpoints suggests that reworking was not a primary concern for their designers. Furthermore, in those instances when broken tips could be reworked, their performance declined. In addition, reworking broken points also resulted in shapes that are uncommon in many arrowpoint assemblages. Our results suggest that the original design attributes of arrowpoints may have been less affected by reworking, and, consequently, may more accurately suggest temporal and behavioral associations. Abstract : Este artículo resume los resultados de los experimentos controlados en los que puntas de proyectil de piedra que varían en la resistencia al impacto en un factor de casi tres se dispararon a materiales que eran cada vez más inelásticos y, por lo tanto, que podían romper las puntas. Las puntas rotas se reformaron si era posible y se volvieron a usar en las mismas condiciones. Nuestros resultados muestran que el daño a los materiales de baja resistencia al impacto, como la obsidiana, fueron generalmente catastróficos, y, en consecuencia, estas puntas rara vez se podian volver a trabajar. El hecho de que piedras de baja resistencia se usaran comúnmente para hacer pequeñas puntas de flecha sugiere que los diseñadores no pensaban en reacondicionarlas. Además, en aquellos casos en que las puntas rotas se pudieran reacondicionar, su rendimiento disminuía. En consecuencia, la reformatización de puntas rotas también dio lugar a formas que son poco comunes en muchos conjuntos de puntas de flecha. Nuestros resultados sugieren que los atributos de diseño originales de las puntas de flecha pueden haberse visto menos afectados por el retoque, y, en consecuencia, pueden sugerir con mayor precisión asociaciones temporales y de comportamiento.